The Peruvian economy in the 80s - Portocarrero, Felipe (1989)
This article presents the evolution of the Peruvian economy in the 80's, a decade that war marked by sharp changes in the economic policy favoured by the authorities. An analysis is provided of the main economic measures adopted by the administrations of Belaunde and Garcia. It is suggested that the economy problems experienced in the 80's were caused by three main factors: the external shock, the stagnation of the export sector and the instability and lack of coherence of the economic policity adopted.